PENGARUH PENERAPAN METODE PEMBELAJARAN AUDITORY INTELLECTUALLY REPETITION TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA KELAS VIII SMP NW ANJANI TAHUN PELAJARAN 2024/2025 - Maysuroh, Nuri; Supriyanto, Supriyanto; Suhamdi, Suhamdi (SINERGI : Jurnal Riset Ilmiah, 2025)
In PAI learning, low communication skills are one of the factors that cause many students to feel dissatisfied because they face difficulties in developing PAI skills. Therefore, improving and developing PAI communication skills needs to be the main focus for every educator in the current learning process. To overcome this, the learning process is carried out using the Auditory Intellectualy Repetition method. T. This study uses a quasi experiment quantitative research type with a pretest-posttest one group design. the results in this study are: there is an effect of the application of the Auditory Intellectualy Repetition method on the learning outcomes of students in the PAI subject of grade VIII JUNIOR HIGH SCHOOL NW Anjani It can be seen from the hypothesis test using the Paired Sample T Test which obtained a sig (2-tailed) value of 0.001. This shows that the significance value or sig (2-tailed) is 0.001 < 0.05 so that the null (Ho) hypothesis is rejected and the alternative hypothesis (Ha) is accepted. While T calculates > t table (9.353>2.015). The t table is obtained from the t-table, while the t- statistic (t-count) is obtained from the results of data tabulation in hypothesis testing.